Integrated transcriptome and microRNA sequencing analyses reveal gene responses in poplar leaves infected by the novel pathogen bean common mosaic virus (BCMV) - Wang, Li; Zhang, Weixi; Shen, Wanna; Li, Min; Fu, Yuchen; Li, Zheng; Li, Jinxin; Liu, Huixiang; Su, Xiaohua; Zhang, Bingyu; Zhao, Jiaping (Frontiers in Plant Science, 2023)
Recently, a novel poplar mosaic disease caused by bean common mosaic virus (BCMV) was investigated in Populus alba var. pyramidalis in China. Symptom characteristics, physiological performance of the host, histopathology, genome sequences and vectors, and gene regulation at the transcriptional and posttranscriptional levels were analyzed and RT‒qPCR validation of expression was performed in our experiments. In this work, the mechanisms by which the BCMV pathogen impacts physiological performance and the molecular mechanisms of the poplar response to viral infection were reported. The results showed that BCMV infection decreased the chlorophyll content, inhibited the net photosynthesis rate (Pn) and stomatal conductance (Gs) and significantly changed chlorophyll fluorescence parameters in diseased leaves. Transcriptome analysis revealed that the expression of the majority of DEGs involved in the flavonoid biosynthesis pathway was promoted, but the expression of all or almost all DEGs associated with photosynthesis-antenna proteins and the photosynthesis pathway was inhibited in poplar leaves, suggesting that BCMV infection increased the accumulation of flavonoids but decreased photosynthesis in hosts. Gene set enrichment analysis (GSEA) illustrated that viral infection promoted the expression of genes involved in the defense response or plant‒pathogen interaction. MicroRNA-seq analysis illustrated that 10 miRNA families were upregulated while 6 families were downregulated in diseased poplar leaves; moreover, miR156, the largest family with the most miRNA members and target genes, was only differentially upregulated in long-period disease (LD) poplar leaves. Integrated transcriptome and miRNA-seq analyses revealed 29 and 145 candidate miRNA‒target gene pairs; however, only 17 and 76 pairs, accounting for 2.2% and 3.2% of all DEGs, were authentically negatively regulated in short-period disease (SD) and LD leaves, respectively. Interestingly, 4 miR156/SPL (squamosa promoter-binding-like protein) miRNA‒target gene pairs were identified in LD leaves: the miR156 molecules were upregulated, but SPL genes were downregulated. In conclusion, BCMV infection significantly changed transcriptional and posttranscriptional gene expression in poplar leaves, inhibited photosynthesis, increased the accumulation of flavonoids, induced mosaic symptoms and decreased physiological performance in diseased poplar leaves. This study elucidated the fine-tuned regulation of poplar gene expression by BCMV; moreover, the results also suggested that miR156/SPL modules played important roles in plant virus disease.